Pengaruh Kompetensi, Inovasi, Pelatihan, Terhadap Kinerja UMKM Center Kabupaten Semarang - Meta Indah Tiara; Sutrisno Sutrisno; M Fadjar Darmaputra (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
This research aims to determine the influence of competency, innovation, training variables on the performance of the Semarang Regency MSME Center. This research has a population of 424 businesses. The sample taken in this research was 108 respondents. Sample collection uses a purposive sampling method with quantitative research methods. This research uses IBM SPSS v24 software to provide factual answers, namely using a number of questionnaires to which respondents have received answers using multiple linear regression data analysis techniques. The results of this research show that competence, innovation and training have a positive and significant effect on business performance. The regression equation obtained Y 25.637. found a positive and significant influence between competence and business performance of 0.230, found a positive and significant influence between innovation and business performance of 0.281, found a positive and significant influence between training and business performance of 0.198. Based on the analysis, the Adjusted R Square value is 0.539, namely 53.9%. shows that the competency, innovation and training variables have an influence of 53.9%, while 46.1% are influenced by other variables, which are not explained in this research.